PERSUASI PADA BAHASA PROMOSI MAJALAH NOVA DITINJAU DARI SEGI PRAGMATIK - Cendriono, Nanang (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2022)
This study aims to describe implicatures that are oriented towards the principle of work in advertising language, and describe speech acts according to Austin’s concept. The approach used is qualitative which is descriptive, so the results of this study contain quotations from data sets that are narrating, exposing, describing, classifying, analyzing, and interpreting. In addition, it also uses a pragmatic approach, which is an approach design that examines the intention of the conversation expressly or impliedly behind the speech being analyzed. The conclusion of this study leads to two things, namely implicature and speech acts. The implicature that is the object of its study is oriented towards the criteria of the principle of cooperation. The working principle is oriented towards quantity maxims, quality maxims, and implementation maxims. The described speech acts are speech acts based on Austin’s concept, namely locution, illocutionary, and perlocutionary speech acts.